Synthesis of Phenanthridinones by Palladium-Catalyzed Cyclization of N-Aryl-2-aminopyridines with 2-Iodobenzoic Acids in Water - Ding, Xiaojuan; Zhang, Lei; Mao, Yiyang; Rong, Binsen; Zhu, Ning; Duan, Jindian; Guo, Kai (Synlett, 2020)
The first Pd-catalyzed cyclization of N-aryl-2-aminopyridines with 2-iodobenzoic acids for the synthesis of phenanthridinones through C–H bond activation under very low catalyst loadings (down to 0.1 mol% Pd) in water is reported. This protocol features a broad substrate scope and provides easy efficient access to various phenanthridinones.
Keywords: phenanthridinones; palladium catalysis; cyclization; arylaminopyridines; iodobenzoic acids